PENGARUH RASIO BUNGA KECOMBRANG (Etlingera elatior) DAN JAHE (Zingiber officinale) TERHADAP MUTU KIMIA MINUMAN FUNGSIONAL WEDANG KECOMBRANG - Maya Eka Pradana; Mazarina Devi; Soenar Soekopitojo (Journal of Food Technology and Agroindustry, 2023)
The purpose of this study was to examine the functional drink wedang kecombrang made from kecombrang flowers, ginger, palm sugar, and water on chemical quality (flavonoids, β-carotene, tocopherols, tannins, and saponins) with different ratios of kecombrang flowers and ginger. This research is a type of experimental research using RAL with 2 repetitions. The data obtained were analyzed using ANOVA analysis of variance and DMRT follow-up test. The results showed that kecombrang wedang with a kecombrang flower : ginger ratio of 2 : 1 had the highest chemical quality including levels of flavonoids, β-carotene, tocopherols, tannins, and saponins with sequential values of 5501.087 mg/L, 123.131315 µg/ml , 6.147095 µg/ml, 1630.313 mg/L, and 356.3625 mg/L.